Analytical techniques in biosciences : from basics to applications - Egbuna, Chukwuebuka; Patrick-Iwuanyanwu, Kingsley C.; Shah, Muhammad Ajmal; Ifemeje, Jonathan Chinenye; Rasul, Azhar (Academic Press, 2022)
"Analytical Techniques in Biosciences: From Basics to Applications presents comprehensive and up-to-date information on the various analytical techniques obtainable in bioscience research laboratories across the world. This book contains chapters that discuss the basic bioanalytical protocols and sample preparation guidelines. Commonly encountered analytical techniques, their working principles, and applications were presented. Techniques, considered in this book, include centrifugation techniques, electrophoretic techniques, chromatography, titrimetry, spectrometry, and hyphenated techniques. Subsequent chapters emphasize molecular weight determination and electroanalytical techniques, biosensors, and enzyme assay protocols. Other chapters detail microbial techniques, statistical methods, computational modeling, and immunology and immunochemistry."--